The transition into work - specialities for the hidden labour force in comparison to other economically inactive persons - Elke Holst; Christa Katharina Spieß (Deutsches Institut für Wirtschaftsforschung (DIW), 2004)
The paper presents a multivariate approach on transitions into work for five non working groups including the unemployed, the Attached, people in education, people doing housework and others. The study is based on ECHP data from 1994 to 1998. It is expected that individuals in the Attached group have significantly higher transition probabilities into work than others outside the labour force although we control for other socio-demographic, economic factors and some macro indicators. Females overall had a lower transition probability into work in all non working groups compared to males. Females in a more conservative country cluster (compared to a less conservative country cluster) had the lowest transition probabilities of all non employed groups. Gender specific differences arose when we took the need to work into account.
Keywords: J6; J2; J4; 330; Hidden Labour Force; Labour Market Attachment; Employment Transition Rates; Labour Market Performance; Berufliche Integration; Berufseinstieg; Versteckte Arbeitslosigkeit; Geschlecht; Frauenerwerbstätigkeit; Schätzung; EU-Staaten